Invitation to environmental sociology - Bell, Michael (Pine Forge Press, 2012)
"The highly praised Fourth Edition of An Invitation to Environmental Sociology brings out the sociology of environmental possibility, inviting students to delve into this rapidly changing field. Written in a lively, engaging style, Michael Bell covers the broad range of topics in environmental sociology with a personal passion rarely seen in sociology textbooks. With extensively updated material on the environmental situation, this edition challenges readers with the complexity of environmental puzzles"--Provided by publisher.